A multidimensional view of intellectual capital: The impact on innovation performance - Mostafa A. Ali; Nazimah Hussin; Hossam Haddad; Reem Al-Araj; Ibtihal A. Abed (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The current economic trend worldwide is for an industrial economy based on tangible assets to convert into a non-tangible economy based on intellectual capital. Lately, a multidimensional view of intellectual capital and its implications on innovation performance have generated renewed research interests. Based on these facts, the relationship amongst different antecedent factors such as culture and trust on intellectual capital components was analysed. In addition, a correlation among intellectual capital components (as non-tangible assets) and innovation performance for the banking sector was established. The positivism philosophy, deductive approach and quantitative methods were used as the research methodology to accomplish the research objectives. In this process, a questionnaire survey and purposive sampling technique were used to collect the responses from 364 employees of the Iraqi commercial banks. The obtained data were analysed statistically using the SPSS v25 and AMOS v24 software. The results revealed a significant impact of culture and trust (antecedent factors) on various intellectual capital components. Furthermore, a strong connection between these antecedent factors and intellectual capital components was evidenced, confirming the study hypotheses. Interestingly, intellectual capital components were found to enhance significantly the innovation performance of the banks, leading to better competitive advantages. In addition, it provided evidence on the impacts of inter-relationships amongst human, structural and relational capitals. Consequently, the study provides academicians and practitioners valuable insights into and guidance on how developing intellectual capital enhances competitive performance, especially in the context of Iraqi commercial banks.
Keywords: 650; culture; human capital; innovation performance; relational capital; social capital; structural capital; trust